UJI EFEKTIVITAS EKSTRAK FLAVONOID DAN STEROID DARI GEDI (ABELMOSCHUS MANIHOT) SEBAGAI ANTI OBESITAS DAN HIPOLIPIDEMIK PADA TIKUS PUTIH JANTAN GALUR WISTAR - Ranti, Gabriela Clementine; Fatimawali, Fatimawali; Wehantouw, Frenly (PHARMACON, 2013)
Abelmoschus manihot L. has been used traditionally as folks medicine plant and it containflavonoid and steroid that has health benefit. The objectives of this research were todetermine anti obesity and hypolipidemic activity of flavonoid and steroid extract fromAbelmoschus manihot L. on white male Wistar induced with high content of protein and lipidfood. Anti obesity test were evaluated by the decreasing of rats weight, whereashypolipidemic test were evaluated by the decreasing of total cholesterol levelsphotometrically using Liebermann-Burchard method. The rats were divided into four groups,namely the negative control (distilled water), extract treatment groups (flavonoids andsteroids), and a positive control group (simvastatin). The percentations of Weight reducingand cholesterol level were analyzed by ANOVA, if there were significant in groups, itcontinued with Duncan Multiple Range Test. The results showed that treatment group possesanti obesity activity, whereas flavonoid extract decrease 7.85% body weight of rats andsteroids extract were 13.70% of body weight. Flavonoids showed hypolipidemic effects bydecrease rats cholesterol levels by 86.45% and steroid extract decrease cholesterol levels by72.53%.Keywords : Abelmoschus manihot L., flavonoid extract, steroid extract, anti obesity,hypolipidemic